LQR Controller Based on BAT Algorithm for Rotary Double Parallel Inverted Pendulum - Le, Thanh-Tri-Dai; Nguyen, Ngoc-Kien; Le, Phuc-Truong; Bui, Minh-Nguyen-Bao; Nguyen, Trong-Tin; Tran, Chi-Anh; Doan, Phuong-Tu; Dao, Duc-Nhan; Nguyen, Van-Dong-Hai; Nguyen, Thanh-Tung (Journal of Fuzzy Systems and Control, 2025)
This paper presents an enhanced approach to stabilizing the Rotary Double Parallel Inverted Pendulum (RDPIP) through a combination of the LQR method and the BAT algorithm. Traditionally, selecting appropriate Q and R matrices relies on designers' intuitions or trial-and-error processes, often resulting in suboptimal performance. By leveraging the BAT algorithm’s swarm intelligence, the proposed method automatically optimizes the cost function to yield improved control performance. Key improvements include shorter stabilization time, reduced overshoot, and minimized oscillations. Simulation results show that the BAT-enhanced LQR controller significantly outperforms traditional design in terms of convergence speed and system damping. These findings underscore the potential of metaheuristic algorithms in refining classical control strategies for complex, nonlinear systems.